ICT IN ENGLISH LANGUAGE TEACHING AND LEARNING - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2021)
The development of information technology, the Internet, directs the history of educational technology in the new groove. Online services in the education of both degree and non-degree are basically providing educational services to users using the Internet as a medium. Online services can be composed of various stages of the process of educational programs.